Electric Load Management Control for Residential Using Internet of Things - Rosli, Muhammad Asyraf; Wahyu Mulyo Utomo (Evolution in Electrical and Electronic Engineering, 2023)
The Internet of Things (IoT) is a cutting-edge technology that has the potential to perform admirably. When it comes to making a decision and doing an evaluation, it is quite helpful to use a tool that was designed for control and observation specifically for monitoring in order to perform monitoring and control work for electrical employees. The objective of this paper is to build a monitoring tool for power systems that can be accessed quickly through an IoT platform and can take input signals from the NodeMCU through the use of a relay that functions as a switch. After that, a check will be made to determine whether there is a power source that can accommodate the load that is being used. Then, signals from the Blynk cloud will be provided via the ESP8266 development board, which will be the primary component of the project. In the online system, there is a switch associated with each connected load that controls the input of the power supply to that load. In addition to being updated in the online system, each piece of linked equipment can be controlled by physical switches, which serve the goal of monitoring the power supply system. An indication is also included with each component that is connected to this system.